Pengaruh Board Structure dan Ownership Structure terhadap Earnings Quality melalui Intellectual Capital Disclosure sebagai Variabel Mediasi - Yuliana Tungabdi; Saarce Elsye Hatane (Business Accounting Review, 2017)
This study aimed to know the direct influence of board structure and ownership structure on earnings quality. In addition, this study also aimed to determine the indirect influence of the board structure and ownership structure on earnings quality by using intellectual capital disclosure as a mediating variable. The sample constituted of 72 manufacturing companies listed on Indonesia Stock Exchange during the period of 2011- 2015. The data was collected from annual reports, which were then analyzed by using WarpPLS version 5.0 software.The finding revealed that there was no significant influence of board structure on earnings quality, but negative influence of ownership structure on earnings quality, positive influence of board structure on intellectual capital disclosure, negative influence of ownership structure on intellectual capital disclosure, and positive influence of intellectual capital disclosure on earnings quality. Furthermore, this study also found that intellectual capital disclosure was able to mediate the impact of board structure on earnings quality, however intellectual capital disclosure failed to mediate the influence of ownersip structure on earnings quality.